PENGARUH EKSTRAK ALPINIA GALANGA (L)WILLD TERHADAP PERTUMBUHAN CANDIDA ALBICANS PADA PLAT GIGI TIRUAN RESIN AKRILIK - Dyaswara Tituk A.W; Uswatun N.A. Darjono; Erwid Fatchur R; Diyah Fatmasari (Jurnal Medali, 2013)
Denture stomatitis disease that occurs in elderly prevented by maintenance and cleaning dentures. Denture stomatitis caused plaque and microorganisms C. albicans that accumulate on surface acrylic resin denture base. Alpinia galanga (L) Willd contains essential oils that are antifungal compounds. This study to determine effectiveness of Alpinia galanga extract to the C. albicans growth on acrylic resin denture plate.This study there was acrylic resin plates 10x10x2 mm soaked in solution of Alpinia galanga (L) Willd extracts concentration 70%, 80%, 90%, and 100% for 8 hour and clorhexidine 0,2% as the positive control. Taken 0.01 ml dripped on petri dishes that is containing SDA and incubated for 48 hours. Next, C. albicans colony counting and data analyzed with Kruskal-Wallis and Mann Whitney.The results Kruskal Wallis showed no significant difference from Alpinia galanga (L) Willd extract concentration 70%, 80%, 90%, and 100% of the growth of C. albicans. Mann Whitney showed difference between the control (+) with every Alpinia galanga (L) Willd extract.The results of this study concluded that extracts Alpinia galanga (L) Willd concentration 70% is the minimum concentration to inhibit the growth of C. albicans maximally.Keyword: Denture stomatitis, Alpinia galanga (L) Willd, C. albicans.